REGN1908‐1909 monoclonal antibodies block Fel d 1 in cat allergic subjects: Translational pharmacokinetics and pharmacodynamics - Mohamed A. Kamal (Wiley, 2021)
Abstract REGN1908‐1909, a 1:1 cocktail of two fully human IgG4 monoclonal antibodies (mAbs), REGN1908 and REGN1909, is being evaluated for treatment of cat allergy. Both REGN1908 and REGN1909 bind to the dominant cat allergen, Fel d 1. Adults with cat allergy confirmed by skin prick test (SPT) were randomized to single subcutaneous administration of placebo (n = 6) or REGN1908‐1909 at doses of 150 (n = 6), 300 (n = 6), or 600 mg (n = 6). Blood samples were taken at prespecified time points for pharmacokinetic (PK) analysis and exploratory evaluation of biomarkers (IgE and SPT). Safety was assessed. Drug concentration‐time profiles in serum for ascending doses of REGN1908‐1909 were consistent with linear PKs. Noncompartmental analysis showed that maximum concentration (Cmax) and exposure increased proportionately with dose, with similar time to maximum concentration (Tmax) for REGN1908 and REGN1909 (6.2 to 8.2 days across doses), and a longer terminal half‐life for REGN1908 (~ 30 days) relative to REGN1909 (~ 21 days). Adverse events were not dose dependent; there were no dose‐limiting toxicities. REGN1908‐1909 is characterized by linear and dose‐proportional kinetics of the two individual mAb components. A single 600 mg dose maintains total mAb mean concentrations in serum above the target (mean of ~ 10 mg/L) for 8–12 weeks. Maintaining this mean target concentration resulted in translational pharmacodynamic effects: maximal mast cell degranulation in a passive cutaneous anaphylaxis mouse model, and maintenance of clinical efficacy measured by Total Nasal Symptom Score in a previous proof‐of‐mechanism study.